FKBP8 protects the heart from hemodynamic stress by preventing the accumulation of misfolded proteins and endoplasmic reticulum-associated apoptosis in mice. (January 2018) - Misaka, Tomofumi; Murakawa, Tomokazu; Nishida, Kazuhiko; Omori, Yosuke; Taneike, Manabu; Omiya, Shigemiki; Molenaar, Chris; Uno, Yoshihiro; Yamaguchi, Osamu; Takeda, Junji; Shah, Ajay M.; Otsu, Kinya
Abstract: Protein quality control in cardiomyocytes is crucial to maintain cellular homeostasis. The accumulation of damaged organelles, such as mitochondria and misfolded proteins in the heart is associated with heart failure. During the process to identify novel mitochondria-specific autophagy (mitophagy) receptors, we found FK506-binding protein 8 (FKBP8), also known as FKBP38, shares similar structural characteristics with a yeast mitophagy receptor, autophagy-related 32 protein. However, knockdown of FKBP8 had no effect on mitophagy in HEK293 cells or H9c2 myocytes. Since the role of FKBP8 in the heart has not been fully elucidated, the aim of this study is to determine the functional role of FKBP8 in the heart. Cardiac-specific FKBP8-deficient ( Fkbp8 −/− ) mice were generated. Fkbp8 −/− mice showed no cardiac phenotypes under baseline conditions. The Fkbp8 −/− and control wild type littermates ( Fkbp8 + /+ ) mice were subjected to pressure overload by means of transverse aortic constriction (TAC). Fkbp8 −/− mice showed left ventricular dysfunction and chamber dilatation with lung congestion 1 week after TAC. The number of apoptotic cardiomyocytes was dramatically elevated in TAC-operated Fkbp8 −/− hearts, accompanied with an increase in protein levels of cleaved caspase-12 and endoplasmic reticulum (ER) stress markers. Caspase-12 inhibition resulted in the attenuation of hydrogen peroxide-induced apoptotic cell death in FKBP8 knockdown H9c2 myocytes. Immunocytological and immunoprecipitation analyses indicate that FKBP8 is localized to the ER and mitochondria in the isolated cardiomyocytes, interacting with heat shock protein 90. Furthermore, there was accumulation of misfolded protein aggregates in FKBP8 knockdown H9c2 myocytes and electron dense deposits in perinuclear region in TAC-operated Fkbp8 −/− hearts. The data suggest that FKBP8 plays a protective role against hemodynamic stress in the heart mediated via inhibition of the accumulation of misfolded proteins and ER-associated apoptosis. Highlights: This study is the first to identify the in vivo role of FKBP8 in the heart. Cardiac-specific FKBP8-deficient mice were generated. FKBP8 plays a cardio-protective role in response to pressure overload. FKBP8 has anti-apoptotic functions via endoplasmic reticulum-mediated pathway. FKBP8 prevents the accumulation of misfolded proteins.